Establishing collaboration and knowledge sharing as a fear of missing out response in improving tourist travel agency innovation performance - Hamdan, Hamdan; Yuliantini, Tine; Raharja, Indra; Samudro, Amzad; Ali, Hapzi (Universitas Negeri Surabaya, Indonesia, 2023)
The FoMO phenomenon usually occurs in individual behaviour on social media. However, recent research in the industrial context has investigated anxiety, fear of being left behind, fear of losing market advantage, and fear of losing competitiveness. This reinforces the still rare term FoMO as an important antecedent of business performance. Highlighting FoMO, as prior research has been limited, is the best way to fill the gap. As a result, an exploratory approach is used, and selecting the SEM-PLS analysis method is the right approach because it is predictive. The results of this study reveal that both direct and indirect effects between FoMO, intention to collaborate, intention to share knowledge, and innovation performance can be accepted and justified empirically. In addition, the mediator of the intention to collaborate is the one that contributes the most to influencing FoMO on the intention to share knowledge. Afterward, the mediator from the intention to share knowledge influences the intention to collaborate on innovation performance. This study confirms that the FoMO concept embedded in the minds of travel agency entrepreneurs is meaningful for success towards competitive innovation performance through the intention to collaborate and share knowledge.